OPTIMASI KINERJA ANALITIK PADA PENENTUAN KADAR FOSFOR SEBAGAI P2O5 PADA ABU BATUBARA DENGAN METODE SPEKTROFOTOMETER VISIBLE - Eka Apriska S Kusuma; Aman Sentosa Panggabean; Yasser Arafat (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
The research on optimization of analytical performance in the determination of phosphorous as P2O5 content in the coal ash with visible spectrophotometer method has been done. In this research was conducted validation visible spectrophotometer method to establish the levels of phosphorus in coal ash. Validation parameters used in this research were accuracy, precision, linearity, LOD, LOQ and ruggedness methods. From the result of this research, accuracy was stated in percent recovery, precision was stated as a RSD percent, withthe equation of linearity as y=0,1768x - 0,0076. From the equation, it will be obtained LOD and LOQ values. And endurance test methods that varied the length of it digest time. From the results it can be concluded that the determination of phosphorous content in the coal ash using visible spectrophotometer method has good precisionand accuracy, and able to be justifiedKeywords: Coal, Phosporous, Analytical Performance, Visible Spectrophotometer.